UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI MELALUI PEMANFAATAN MEDIA FILM - Euis (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
The background of this research Students’ class XI IPS 2 Madrasah Aliyah YPK Cijulang Kabupaten Pangandaran learning outcomes in sociology subject were still in low category, students who have not reached KKM reached 87.5%. This study aims to improve the learning outcomes of class XI IPS at Madrasah Aliyah YPK Cijulang Pangandaran in the 2019/2020 school year on sociology through the use of film media. The method used in this research was classroom action research which was carried out in two cycles. The data sources came from the teachers and students. This study employed observation and test to collect the data collection using observation and test techniques. Data analysis was carried out qualitatively and quantitatively. The results showed that students’ learning outcomes increased from pre-cycle, cycle I and cycle II. The completeness percentage was 12.5% ​​in the pre-cycle, increasing to 44.82% in the first cycle and increasing to 75% in the second cycle. The class average score of students in the pre-cycle 61.05 increased to 72.33 in the first cycle and increased to 76.84 in the second cycle. From the result, it can concluded that the use of film media can improve the learning outcomes for sociology of conflict and violence material for students of class XI IPS 2 Madrasah Aliyah YPK Cijulang Pangandaran Regency in the 2019/2020 academic year.